PENGEMBANGAN PERTANIAN BERKELANJUTAN BERBASIS PUPUK ORGANIK PADAT PADA KELOMPOK TANI DESA BONGOHULAWA KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - silvana Apriliani; Nurdin Nurdin; Rival Rahman (Jurnal Abdi Insani, 2023)
Currently, many people know that the use of inorganic materials in plant cultivation can have negative effects on human health and the environment. So it is very necessary to increase plant productivity by implementing organic plant cultivation technology that is sustainable and environmentally friendly. Bongohulawa Village, Tilongkabila District, Bone Bolango Regency is a village where some of the population is engaged in farming and animal husbandry, but the farming community does not utilize livestock manure and plant litter waste which is used as a basic ingredient for making solid organic fertilizer. The aim of the community service activity is to provide training in making solid organic fertilizer from cow manure and rice straw litter in Bongohulawa village, Bone Bolango subdistrict. The methods used in this activity are the material provision stage and the training stage. The training stage involves carrying out demonstrations in making solid organic fertilizer for farmer groups using cow manure, rice straw litter, EM4 bioactivator as basic ingredients. During community service activities, most farmer groups have problems with a lack of knowledge about fertilizers made from organic raw materials such as cow dung waste and rice straw waste which can improve the physical, chemical and biological properties of the soil so that the farmer group community has high enthusiasm because of the material and training regarding Making organic fertilizer and rice straw is something new for farmer groups. It is hoped that the technology provided to farmer groups can be implemented when cultivating plants, in order to produce food and a healthy and sustainable environment. In conclusion, this solid organic fertilizer activity can be applied to improve soil fertility, increase production and can open up business opportunities for organic fertilizer in attractive packaging with high selling value.